Ảnh hưởng của đặc điểm hội đồng quản trị đến hành vi quản trị lợi nhuận của các công ty gia đình niêm yết trên thị trường chứng khoán Việt Nam trước và trong đại dịch COVID-19 - Hoàng Cẩm, Trang; Nguyễn Thu , Thủy; Nguyễn Thị Như , Hảo (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Earnings management plays a significant role within the operational management process, aimed at facilitating the supervisory function of the Board of Directors (BOD) over profit-related matters. Nevertheless, in pursuit of their objectives, the BOD may exploit accounting tools to manipulate financial reporting in a direction advantageous to the executive members, particularly emanating from family-owned firms, exacerbated notably by the impact of the COVID-19 pandemic. Therefore, this paper examines four characteristics of BOD that influence earnings management in family-owned firms listed on the Vietnamese stock market before and during the COVID-19 pandemic. The data consists of 123 family firms listed on the Ho Chi Minh City Stock Exchange and the Hanoi Stock Exchange from 2016 to 2021, resulting in 738 observations. The study reveals that BOD size and BOD independence negatively impact earnings management; whereas expertise in financial accounting, and the frequency of BOD meetings positively impact earnings management during the COVID-19 period. Additionally, BOD size and BOD independence in the pre-COVID-19 period do not influence earnings management.